Rancang Bangun Phantom Ultrasonography Untuk Kalibrasi Ultrasonography (USG) - Christopher Bagaskoro; Abdul Haris Kuspranoto (LPPM POLBITRADA, 2025)
This study aims to design and build an Ultrasonography (USG) Phantom as an ultrasound calibration medium with more affordable materials but still meets quality and precision standards. The USG Phantom is designed using two basic materials, namely distilled water and engine oil, to then compare its performance in producing ultrasonic images. The research method used is an experiment with the stages of tool design, phantom manufacturing, and functional testing using Vertical and Horizontal Distance parameters. Testing was carried out with a convex USG transducer at Roemani Muhammadiyah Hospital Semarang. The test results show that the engine oil-based phantom provides a clearer and more stable image compared to water. The results of vertical distance measurements show the smallest absolute error value of 0.01cm (0.1mm) on objects 1–2 with a relative error value of 0.3%, and the largest of 0.09cm (0.9mm) on objects 7–8 with a relative error value of 4.5%. Meanwhile, for horizontal distance, the smallest absolute error value was recorded at 0.14 cm (1.4 mm) on objects 1–2 with a relative error value of 6.8%, and the largest was 0.19 cm (1.9 mm) on objects 2–3 and 4–5 with a relative error value of 9.5%. All vertical and horizontal error values ​​were still within the AAPM TG‑1 tolerance limits, which were ±2 mm or ±2% for vertical measurements and ±3 mm or ±3% for horizontal measurements. Thus, the engine oil phantom can be categorized as a suitable ultrasound calibration medium that is economical, effective, and meets international accuracy standards. This research is expected to be a practical solution for healthcare facilities to perform ultrasound calibration at a lower cost.